The Effect of Giving Salak Fruit Powder Brewing (Salacca dumatrana) to Reduce Nausea and Vomiting in Pregnant Women - Nasution, Izmi Fadhilah; Insan, Hafni Nur; Batubara, Rini Amalia (Jurnal Kebidanan, 2025)
Nausea and vomiting in pregnancy is a common condition in pregnancy, 80% of pregnant women experience symptoms of nausea and vomiting ranging from mild to severe. This study aims to determine how to overcome nausea and vomiting non-pharmacologically by using the local wisdom of Padangsidimpuan City, consuming snake fruit. Snake fruit also contains flavonoids which are useful for increasing bile production and neutralizing digestive fluids which can reduce nausea and vomiting in pregnant women. The quantitative research design uses the paired sample test. Sampling with a total sampling technique of 50. The study was conducted at the Sadabuan Health Center, Padangsidimpuan City in 2024. The results of the study showed that there was no difference in the average nausea in pregnant women for the pre-test control group with the post-test control group . There was no difference in the average vomiting in pregnant women for the pre-test control group with the post-test control group (p = 0.627> 0.005). There was a difference in the average nausea in pregnant women for the pre-test experimental group with the post-test experimental group (p = 0.000 <0.005). There was a difference in the average vomiting in pregnant women for the pre-test experimental group with the post-test experimental group (p = 0.000 <0.005). The conclusion is that there is an effect of giving snake fruit powder in reducing nausea and vomiting in the experimental group.